2015
DOI: 10.1111/inr.12170
|View full text |Cite
|
Sign up to set email alerts
|

Physical and verbal workplace violence against nurses in Jordan

Abstract: Physical and verbal workplace violence in Jordan, like other countries, is a dangerous behavior that negatively affects general hospital nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
4
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 18 publications
3
59
4
9
Order By: Relevance
“…The findings of this study revealed that patients and their families were the most frequent perpetrators of violence against nurses. This finding is inconsistent with the findings of other studies examining WPV in healthcare settings (Al‐Omari ; Cashmore ; Fujishiro et al. ; Pai & Lee ; Taher ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of this study revealed that patients and their families were the most frequent perpetrators of violence against nurses. This finding is inconsistent with the findings of other studies examining WPV in healthcare settings (Al‐Omari ; Cashmore ; Fujishiro et al. ; Pai & Lee ; Taher ).…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of this study revealed that patients and their families were the most frequent perpetrators of violence against nurses. This finding is inconsistent with the findings of other studies examining WPV in healthcare settings (Al-Omari 2015;Cashmore 2012;Fujishiro et al 2011;Pai & Lee 2011;Taher 2010). Fujishiro et al (2011) revealed that nursing colleagues, seniors, managers and doctors were the primary sources of WPV.…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence of physical and verbal violence against Iranian nurses was 28% and 74%, respectively. The study findings in neighboring countries show that the prevalence of physical and verbal violence is respectively 74.9% and 91.4% in Turkey (43), and 52.8% and 67.8% in Jordan (44), which are higher when compared to the prevalence in Iran. The results of Abu al -Rub et al (2007) study showed that the prevalence of physical violence against Iraqi nurses was 42.2%, from which 14.3% were carried out with deadly weapons (45).…”
Section: Discussionmentioning
confidence: 86%
“…5 6 Several substantial studies have suggested that nurses have a high risk of experiencing WPV. [6][7][8][9][10] During the past 12 months, the incidence rate of physical violence for nurses in Ethiopia, 7 South Korea, 8 Jordan, 9 Germany 10 and Iran 3 ranged from 18.22% to 56.0%, the verbal abuse rate being from 63.8% to 89.58% and the sexual harassment rate from 4.7% to 19.7%. WPV occurs primarily in the emergency wards and psychiatric departments of hospitals.…”
Section: Introductionmentioning
confidence: 99%